Research of Improving the Service Quality of Home-Care Long-Term Care Institutions - Hung, Jui-Ying (Journal of Posthumanism, 2025)
The research aims to analyze the empirical data of the evaluation results from home-care long-term care (LTC) service institutions to understand the status of home-care institutions in Taiwan. Based on the results of analysis will be used as an empirical study to revise the evaluation benchmark in 2026. Based on the on-site evaluation results of 50 home-based LTC institutions, 26% excellent (evaluation score ≧ 85), and 14% un-qualified (evaluation score < 70). The results were based on the "coincidence rate to be improved" as the key failure factors (KFF) of home-based LTC institutions. Compared with the consensus benchmark of each concept, KFF accounted for 60% of the professional care quality concept, indicating that the professional care quality profile had a significant impact on the evaluation results of home-based LTC institutions. Suggested that home-care institutions integrate cross-disciplinary resource differences based on self-improvement and case-based in response to the evaluation preparation.